USE OF PSYCHOACTIVE SUBSTANCES AND ACADEMIC PERFORMANCE OF UNIVERSITY STUDENTS IN THE HEALTH AREA - Sousa, Francisco Matheus Azevedo de; Sousa, Larissa Maria Dantas de; Aragão, Joyce Mazza Nunes; Oliveira, Eliany Nazaré; Almeida, Paulo César de; Bezerra, Soleane Mazza Nunes; Vasconcelos, Maristela Inês Osawa (Cogitare Enfermagem, 2023)
Objective: to verify the most prevalent psychoactive substances used among undergraduate students in the health area and their interference in academic performance. Methods: a total of 115 Nursing and Physical Education students from a public university in inland Ceará, Brazil, answered the Drug Use Screening Inventory questionnaire in 2021. To analyze the results, Pearson’s chi-square and likelihood ratio statistical tests were used. Results: a total of 65 (56%) students used analgesics, 54 (47%) drank alcohol and 14 (12.2%) smoked marijuana. There was no statistical association between use of psychoactive substances and academic performance. However, among those who used analgesics or alcohol, more than 1/3 analyzed their performance as poor/terrible or fair, and half of those who smoked marijuana analyzed it in the same way. Conclusion: the study contributed to understanding the psychoactive substances prevalent in the university context and associated aspects, emphasizing the need for interventions.